Analisis Pelayanan Retribusi Daerah Izin Mendirikan Bangunan (IMB) Dalam Tercapainya Kualitas Pelayanan Publik yang Optimal di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Medan - Wahyuni Lubis; Aninda Zahra; Arnida Arnida (VISA: Journal of Vision and Ideas, 2023)
The purpose of this study is to know and analyze the implementation of services and the IMB levy budget, especially in the service of building permits in the investment office and one-stop integrated service in Medan City. The type of survey conducted is qualitative with a descriptive approach. Data collection techniques used direct interviews, observations and documents in the form of documents, archives, and literature related to the quality of IMB services and public services at BPPT Medan City. The data analysis carried out is a qualitative analysis with a descriptive approach. The result is that the Medan City BPPT in the implementation of IMB services is going well, although there are still some obstacles faced in optimizing the quality of public services in order to achieve the quality of public services. It shows that. Human resources and infrastructure. Conclusion Based on the survey, IMB services at BPPT Medan Cit y have been implemented well, but there are some aspects that are not optimal. To improve the quality of public services in a more optimal direction, we need to be efficient, economical and minimize the obstacles we face . Keywords: Building Permit , IMB Retribution Budget, Public Servic